Guidance for the decontamination of intracavity medical devices: the report of a working group of the Healthcare Infection Society. Issue 1 (January 2019) - Bradley, C.R.; Hoffman, P.N.; Egan, K.; Jacobson, S.K.; Colville, A.; Spencer, W.; Larkin, S.; Jenks, P.J.
Summary: Background: Intracavity medical devices (ICMDs) are used in a wide variety of healthcare settings. The approach to their decontamination and the resources available also differ widely. Their potential for infection transmission is considerable. Aim: To produce a comprehensive risk assessment-based approach to the decontamination of ICMDs, accompanied by an adaptable audit tool. Key recommendations: – All ICMDs should be classified according to the risks of infection transmission they pose. – The processes used for their decontamination should conform to a basic essential quality requirement, with progression towards a higher quality best practice. – After each use, all probes should initially be thoroughly cleaned. – Those probes with mucous membrane contact should be disinfected in a controlled process. – Manual disinfection would comply with essential quality requirements; validated automated disinfection would constitute best practice. – Areas of the probe and its associated parts that make contact with an operator's contaminated hand also require decontamination. – Probes in contact with sterile body tissue should be sterilized; use of sterile barriers alone is unacceptable. – All those who decontaminate ICMDs should be trained to do so. – Decontamination should occur in facilities adequately equipped and allowing a defined dirty to clean flow pathway. – There should be a documentation system that allows tracking and tracing of each probe to the patients it is used on and each episode of its decontamination. – That a healthcare provider can supply adequate decontamination should be established before a new ICMD is acquired. – The process of ICMD decontamination should be regularly audited.